Findings of CSF Examination in Lethargic Neonates - Marjana Dritan Sabri; Fatime MimozaX hafer; Aida Shpresa Ramazan (Academic Journal of Clinicians, 2022)
There is no specific criteria could be identified to predict which newborn having meningitis or sepsis ,so CSF examination and blood culture are mandatory and crucial tests for lethargic neonate. This study aimed to predict the incidence of meningitis and sepsis in newborn baby who have clinically letharginess and to define the risk factors such as gestational age ,onset and duration of rupture membrane and other maternal risk factors. This study was carried out in the National Center for Children's Development, Albania during 6 months (January-June 2019) included (40) patients aged ≤ 28 days who were admitted during this period to NICU with letharginess, (21) patients were full-term and (19) patients were preterm, male neonates were 22. Out of the 40 neonates, (32) aged 1-7 days and (8) neonates aged 8-28 days , (10) of them delivered by C/S and (30) by NVD . Mothers’ history of leaking liqour for more than 18 hours before the onset of labour reported in 22 cases while it was for less than 18 hours in the remaining 18 cases. CSF and blood culture were performed for all neonates as a part of infectious screen. Two neonates (5%), diagnosed as having meningitis according to the abnormal CSF findings and positive culture and 16 patients (40%) diagnosed as neonatal sepsis according to the positive blood culture. The remaining 22 patients(55%) showed Negative CSF and blood cultures which indicated that lethargy is common evidence of many other neonatal diseases. In conclusion, incidence of neonatal infections are common in premature newborn and in newborn with maternal risk factors. The incidence of neonatal sepsis most common than neonatal meningitis the ratio was 8:1.